Iron regulates ferritin mRNA translation through a segment of its 5' untranslated region. - Aziz, N (1987)
In previous studies, we showed that acute administration of iron to intact rats or to rat hepatoma cells in culture induces synthesis of the iron-storage protein ferritin by activating translation of inactive cytoplasmic ferritin mRNAs for both the heavy (H) and the light (L) subunits. In the course of activation, these ferritin mRNAs are recruited onto polysomes. To elucidate the structural features of these mRNAs involved in the translational response to iron, a chimera was constructed from the 5' and 3' untranslated regions (UTRs) of ferritin L subunit mRNA fused to the reading frame of the mRNA of bacterial chloramphenicol acetyltransferase (CAT). This chimera and deletion constructs derived from it were introduced into a rat hepatoma cell line by retrovirus-mediated gene transfer. The complete chimera showed increased CAT activity in response to iron enrichment of the medium, whereas deletion of the first 67 nucleotides of the 5' UTR, which contain a highly conserved sequence, caused loss of regulation by iron. Whereas cis-acting sequences located in the 5' flanking regions of many genes have been repeatedly implicated in modulating their transcriptional expression, we report here a specific regulatory translational sequence found within the 5' UTR of a eukaryotic mRNA.